Evaluación maderable de un bosque con fines de aprovechamiento sostenido de la zona de Buen Jardín distrito Yavarí. Loreto Perú, 2021 - Vela Saldaña, Jhoset Guillermo (2022)
The study was carried out in the forests of the “Buen Jardin” area, Yavarí district - Loreto Region. The objectives were to record the floristic composition of commercial species with diameter ? 40 cm; determine the IVI; define the volume of standing commercial timber and the economic valuation. The population. The study area was in total (ha): 500.00 from the forests of "good garden" district of Yavarí. The sample was 250.00 (ha). The methodology used to do the field work was the design of a random inventory. 9 commercial species were found, distributed in 7 botanical families. The largest number of species is in the botanical family Myristicaceae, Fabaceae. The abundance of commercial species is in the Fabaceae family, which represents 51.61% and 12.44% of the total species registered in the forest inventory of the study area; The dominance of the commercial species is 133.97 m2 / ha. The most frequent species are “aguano cumala, cedar, cumala”. The representative species, according to the IVI are, "Tornillo, aguano cumala and cumala". The volume of commercial wood is 7.68 m3 / ha. The species with the highest Valuation per hectare is the Tornillo with S /. 533.22 soles.